Proteínas do soro sanguíneo de cães inoculados com veneno de Tityus serrulatus - E.L. Ribeiro; M.M. Melo (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2012)
Protein profile of twelve healthy adult dogs averaging 14.2±5.4kg was evaluated after the inoculation of yellow scorpion venom (Tityus serrulatus). The animals were randomly divided in two experimental groups (G) (n= 6): GI control, which received 0.5mL of phosphate buffered saline (PBS) subcutaneously in the medial side of the left thigh (MSLT), and GII which received T. serrulatus venom (250μg/kg), diluted in 0.5mL of PBS subcutaneously in the MSLT. Blood samples were collected before the venom inoculation (time zero) and after 2, 6, 12, 24, 48 and 72h to obtain serum for measurement of total proteins. The fractionated protein profile was done by electrophoresis on agarose films using Tris and Amido Black staining and quantification of albumin and globulin fractions by software. The results showed no changes in the levels of total proteins, albumin and α, β and γ globulin or reversal of the albumin:globulin ratio between the groups, concluding that the dose of 250μg/kg of Tityus serrulatus venom did not induce acute phase proteins in dogs.